Respuesta :

Answer:

D.  17,15,13,11

Step-by-step explanation:

The expression states that the next term in this sequence is formed by subtracting 2 from the preceding (n-1) result.  We know that for n = 1 that f(1) = 17.

f(n) is f(n-1) - 2

so

f(2) = f(1) - 2

f(2) = 17 - 2 or 15

f(3) = f(2) - 2

f(3) = 15 - 2 or 13

f(4) = f(3) - 2

f(4) = 13 - 2 or 11

 . . . .

 . . . .

 . . . .

and so on.

Answer:

D and B

Step-by-step explanation:

using the recursive formula and f(1) = 17 , then

f(2) = f(1) - 2 = 17 - 2 = 15

f(3) = f(2) - 2 = 15 - 2 = 13

f(4) = f(3) - 2 = 13 - 2 = 11

first 4 terms are 17, 15, 13, 11 → D

-------------------------------------------------------

Using the recursive formula and f(1) = 5 , then

f(2) = 4f(1) = 4 × 5 = 20

f(3) = 4f(2) = 4 × 20 = 80

f(4) = 4f(3) = 4 × 80 = 320

first 4 terms are 5, 20, 80, 320 → B